Short-term of mortality in acute stroke patients (Bangladesh Journal of Medicine, 2023)
Background: Stroke is a major cause of disability and death. A significant number of patients with acute stroke dies within 30 days of developing stroke. The aim of the study was to determine the short-termmortality (within 30 days) in acute stroke patients.Methods: This was a cross-sectional study, carried out in the Department of Medicine of Rangpur Medical College Hospital. Date was collected for 6 months (from January to June).Results: During the study period, we studied of 248 acute stroke patients, among them 110 were hemorrhagic and 138 were ischemic. Mean age of the patients were 56.02 years in hemorrhagic stroke and 61.26 years in ischemic stroke. In case of hemorrhagic stroke, short term mortality was 45.5% (50), among them in hospital death was 88% (44) and majority of the deaths occurred with in the first 7 days. Mortality was significantly higher among patients with larger hematomas (>60 cm3) compared to subjects with smaller hematomas (